Investigating the Causal Relationship Between Physical Activity and Chronic Back Pain: A Bidirectional Two-Sample Mendelian Randomization Study - Gao, Shaowei; Zhou, Huaqiang; Luo, Siyu; Cai, Xiaoying; Ye, Fang; He, Qiulan; Huang, Chanyan; Zheng, Xiaoyang; Li, Ying; Du, Zhanxin; Wang, Yaqing; Qi, Zhihui; et al. (Frontiers in Genetics, 2021)
Background: Recent observational studies have reported a negative association between physical activity and chronic back pain (CBP), but the causality of the association remains unknown. We introduce bidirectional Mendelian randomization (MR) to assess potential causal inference between physical activity and CBP. Materiasl and Methods: This two-sample MR used independent genetic variants associated with physical activity and CBP as genetic instruments from large genome-wide association studies (GWASs). The effects of both directions (physical activity to CBP and CBP to physical activity) were examined. Inverse variance-weighted meta-analysis and alternate methods (weighted median and MR-Egger) were used to combine the MR estimates of the genetic instruments. Multiple sensitivity analyses were conducted to examine the robustness of the results. Results: The MR set parallel GWAS cohorts, among which, those involved in the primary analysis were comprised of 337 234 participants for physical activity and 158 025 participants (29 531 cases) for CBP. No evidence of a causal relationship was found in the direction of physical activity to CBP (odds ratio [OR], 0.98; 95% CI, 0.85-1.13; P = 0.81). In contrast, a negative causal relationship in the direction of CBP to physical activity was detected (β = -0.07; 95% CI, -0.12 to -0.01; P = 0.02), implying a reduction in moderate-vigorous physical activity (approximately 146 MET-minutes/week) for participants with CBP relative to controls. Conclusion: The negative relationship between physical activity and CBP is probably derived from the reduced physical activity of patients experiencing CBP rather than the protective effect of physical activity on CBP.